Youth Mobilisation as Social Navigation. Reflections on the concept of dubriagem - Henrik Vigh (Cadernos de Estudos Africanos)
This article sheds light on the mobilisation of young people into conflict. It argues that warfare constitutes a terrain of possibility for urban youth in Guinea-Bissau, and shows how they navigate war as an event by tactically manoeuvring within the social ties and options that arise in such situations. Building on the Guinean Creole term of dubriagem, the article proposes the concept of social navigation as an analytical optic able to shed light on praxis in unstable environments. The concept of social navigation makes it possible to focus on the way we move within changing social environments. It is processuality squared, illuminating motion within motion. The article thus advocates an analysis of praxis that takes its point of departure in a Batesonian and intermorphological understanding of action in order to further our understanding of the acts of youth in conflict.